2012
DOI: 10.1016/j.talanta.2012.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a tunable glucose biosensor based on zinc oxide/chitosan-graft-poly(vinyl alcohol) core-shell nanocomposite

Abstract: A potentiometrically tuned-glucose biosensor was fabricated using core-shell nanocomposite based on zinc oxide encapsulated chitosan-graft-poly(vinyl alcohol) (ZnO/CHIT-g-PVAL). The glucose oxidase (GOD) was immobilized onto ZnO/CHIT-g-PVAL coated indium-tin oxide (ITO) glass substrate. The electrostatic interaction between GOD and ZnO based core-shell nanocomposite provided the resulting tuned enzyme electrode (GOD/ZnO/CHIT-g-PVAL) with a high level of enzyme immobilization and excellent lifetime stability. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(28 citation statements)
references
References 30 publications
1
26
0
1
Order By: Relevance
“…Thus, the high GCSPs of sensor confirmed that large quantity of GOx was immobilized on the porous electrode than that of SCS electrode. Moreover, the addition of Pt over ZnO nanoporous has improved the catalytic nature and acts as an excellent electron mediator and which accelerates the electron transfer between GOx and electrode[21].The detection limit (LOD) for ZnO/Pt/GCSPs/GOx was 0.03 mM and 0.09 mM for ZnO/Pt/SCS/GOx at a signal to noise ratio of 3 which was comparable with already reported enzyme based glucose…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Thus, the high GCSPs of sensor confirmed that large quantity of GOx was immobilized on the porous electrode than that of SCS electrode. Moreover, the addition of Pt over ZnO nanoporous has improved the catalytic nature and acts as an excellent electron mediator and which accelerates the electron transfer between GOx and electrode[21].The detection limit (LOD) for ZnO/Pt/GCSPs/GOx was 0.03 mM and 0.09 mM for ZnO/Pt/SCS/GOx at a signal to noise ratio of 3 which was comparable with already reported enzyme based glucose…”
supporting
confidence: 78%
“…To enhance the direct electron transfer from GOx enzyme to sensitive layer, a functional material is required to attain their excellent performance. Zinc oxide (ZnO) is one among such versatile nanomaterial with low dimensionality and inadequate properties like biocompatibility, non-toxicity, electric conductivity, high electron transfer etc., which provides an incentive to the research and development especially in biomedical and sensor applications [21,22]. Moreover, metallic nanoparticles have been considered much in the field of catalysis and sensor due to its better catalytic and sensing properties than nonmetallic components.…”
mentioning
confidence: 99%
“…This demonstrated the feasibility of using a single 1D nanostructure as a nanoprobe for biosensing in single cells or microorganisms [47]. A core-shell nanocomposite based on ZnO encapsulated by chitosan-graft-poly (vinyl alcohol) (PVA) was used to fabricate a potentiometrically-tuned glucose biosensor [54]. It exhibited fast surface-controlled redox biochemistry, with a detection limit of 0.2 μM, a linear range of 2 μM-1.2 mM, and a sensitivity of > 0.04 V μM −1…”
Section: Zno-based Nanocomposites For Gox Immobilizationmentioning
confidence: 99%
“…The synthesis of new ZnO nanostructures should be guided by the potential for an improved device. Many biosensors containing ZnO or ZnO-based nanocomposites exhibit DET, without the presence of mediators [9,[11][12][13]54,57,60,61,77,78]. Investigating DET is important for understanding the kinetics and thermodynamics of biological redox processes, and for fabricating next-generation biosensors.…”
Section: Science China Materialsmentioning
confidence: 99%
“…It is a hydrophilic material due to the presence of both amino and hydroxyl groups; however, CHIT is insoluble in water and aqueous basic media [33]. It was chosen as the orientation directing matrix because there are large quantities of amino and hydroxyl groups on the CHIT units, which have a strong binding ability to enzyme [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%